Simulation of Pedestrian Walking Through Angled-Corridors for Evacuation Behaviour Study. Issue 1 (June 2020) - Rahman, N A; Alias, N A; Sukor, N S A; Halim, H; Gotoh, H; Hassan, F H
Abstract: The effect of acute- and obtuse-angled-corridors on the evacuation behaviour is rarely studied. In the previous work, we have confirmed that corridor with less than 90° turning angle has negative impact to the pedestrians walking behaviour due to the tendency of the pedestrians to slow down their motion when approaching the turning of the corridor. This restrict the flow of walkers during high-density situation and cause congestion near that turning of the corridor. In this contribution, empirical data collected from previous experimental work is utilised to further study the effect of turning angle on the evacuation behaviour. The simulations of walking through angled-corridor were reproduced which reflects evacuation scenarios. Three different types of angled-corridor are taken into consideration (a 60°-, a 90°-, and a 135°-angled-corridors) with different sets of number of pedestrians (NOP: 60, 70, 80, 90 and 100). Three metrics of evacuation behaviour measurement are reported: (1) inflexion points, (2) escape time, and (3) interaction force. Inflexion point is used to evaluate the restriction flow occurred during the evacuation. From the results, the 60° angled-corridor contained the highest number of inflexion points. With the highest number of inflexion points, the escape time for the 60° angled-corridor is 14.8% to 24% longer compared to the other two types of angled-corridors. This shows that this kind of angled-corridor need to be avoided in the future design of walkways. On top of that, the 60° angled-corridor also gives the maximum interaction force with 213.75 N. This reconfirmed that the corridor with less than 90° turning angle is not suitable to be built as a walkway. This work is relevant to be studied due to its immediate applications in assessment of crowd safety for building egress.